Exosomes, Their Biogenesis and Role in Inter-Cellular Communication, Tumor Microenvironment and Cancer Immunotherapy - Kishore Kumar Jella; Tahseen H. Nasti; Zhentian Li; Sudarshan R. Malla; Zachary S. Buchwald; Mohammad K Khan (Vaccines, 2018)
Exosomes are extracellular vesicles ranging from 30 to 150 nm in diameter that contain molecular constituents of their host cells. They are released from different types of cells ranging from immune to tumor cells and play an important role in intercellular communication. Exosomes can be manipulated by altering their host cells and can be loaded with products of interest such as specific drugs, proteins, DNA and RNA species. Due to their small size and the unique composition of their lipid bilayer, exosomes are capable of reaching different cell types where they alter the pathophysiological conditions of the recipient cells. There is growing evidence that exosomes are used as vehicles that can modulate the immune system and play an important role in cancer progression. The cross communication between the tumors and the cells of the immune system has gained attention in various immunotherapeutic approaches for several cancer types. In this review, we discuss the exosome biogenesis, their role in inter-cellular communication, and their capacity to modulate the immune system as a part of future cancer immunotherapeutic approaches and their potential to serve as biomarkers of therapy response.